Enigma of social media use: complexities of social media addiction through the serial mediating effects of emotions and self-presentation - Ho, Wing W. Y.; Lau, Yan H. Y.; Leung, Leona Y. L.; Li, Eric K. L.; Ma, Reyna K. K. (Frontiers in Psychology, 2024)
Introduction Excessive social media use, though considered unhealthy, is no longer formally categorized as an addiction or disorder, leading to a lack of consensus on this behavior. It raises concerns regarding the exclusion of Internet Addiction Disorder from the DSM-5-TR due to insufficient empirical evidence. This study investigates the serial mediating effects of positive and negative affect, fear of missing out, and offline and online self-presentation in the relationship between social media use and social media addiction. Method The study was conducted in Hong Kong with 385 participants (84.2% F, age range = 18–60) of an online survey. This study administered the Social Media Use Scale, Positive and Negative Affect Schedule, Fear of Missing Out Scale, Presentation of Online Self Scale, and Bergen Social Media Addiction Scale. Results The results indicate that social media use plays a significant role in predicting both positive and negative affect. The findings further reveal that positive and negative affect, fear of missing out, and offline and online self-presentation act as serial mediators in the relationship between social media use and social media addiction. In other words, these variables work together in a sequential manner to mediate the impact of social media use on addiction. Additionally, the study indicates that social media use and social media addiction are fully mediated by both positive and negative affect, fear of missing out, and offline and online self-presentation. Discussion Social media use can evoke both positive and negative affect. The longer individuals are immersed in social media, the more their positive affect intensifies, exacerbating FoMO and fostering inconsistent offline and online self-presentation. Conversely, extended social media engagement can heighten negative affect, leading to anxiety about others having more rewarding experiences and concurrently inducing apprehension characterized by FoMO. To prevent addiction, the development of educational tools such as SimCity video games, scenario-based learning activities, and virtual reality experiences focused on social media use and social media addiction can offer a valuable opportunity for pre-exposure to the related risks and challenges.